2020
DOI: 10.1080/02670836.2020.1818511
|View full text |Cite
|
Sign up to set email alerts
|

Improved properties of dual-phase steel via pre-intercritical annealing treatment and thermal cycling

Abstract: The synergistic effects of pre-intercritical annealing treatments and multiple heating to the two-phase region (followed by quenching) on the microstructure and mechanical properties of dual-phase (DP) steel were studied. Intercritical annealing of ferritic-pearlitic, martensitic, and cold-rolled martensitic microstructures was investigated. The effects of tempering, austenitisation, grain growth, and recrystallisation were unravelled and an optimum holding time was characterised for each initial microstructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…These values fit within the usual mechanical properties of DP steel [4]. Compared to the previous studies of DP steel processed with various heat treatment conditions [5][6][7][8][9][10][11][12][13][14][15][16][17][18], the results are comparable although direct comparison is not precise due to the difference in the tensile testing condition. It was suggested that tailoring the microstructure with cold deformation before intercritical annealing promotes recrystallization and leads to better mechanical properties [5,8,9,12].…”
Section: Relationship Between Microstructure and Mechanical Propertiessupporting
confidence: 75%
See 2 more Smart Citations
“…These values fit within the usual mechanical properties of DP steel [4]. Compared to the previous studies of DP steel processed with various heat treatment conditions [5][6][7][8][9][10][11][12][13][14][15][16][17][18], the results are comparable although direct comparison is not precise due to the difference in the tensile testing condition. It was suggested that tailoring the microstructure with cold deformation before intercritical annealing promotes recrystallization and leads to better mechanical properties [5,8,9,12].…”
Section: Relationship Between Microstructure and Mechanical Propertiessupporting
confidence: 75%
“…Out of many heat treatment methods, multiple cycles annealing [16][17][18], is incredibly interesting. It was reported that grain size reduction was achieved by cyclic intercritical annealing which enhances the mechanical properties [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another processing route for adjusting the microstructure and mechanical properties of DP steels is called thermal cycling (TC). It is a repetition of the intercritical annealing with subsequent quenching (IA route) as done in [54][55][56][57][58][59][60][61][62][63][64]. Ghaemifar and Mirzadeh [49,59] applied a repetitive intercritical annealing on a ferritic-pearlitic banded steel and revealed that the band spacing of microstructure could be reduced via the thermal cycles and reached then a saturated value after some passes.…”
Section: Initial Microstructurementioning
confidence: 99%
“…As an effective approach to reduce or eliminate the microsegregation of alloying elements and promote the dissolution of low melting point phases, homogenization treatment can significantly improve the hot working plasticity of the alloy and effectively avoid hot working cracking. [21,22] Xie et al investigated the effects of different homogenization temperatures on the microstructure and NbC dissolution behavior of Nb-containing as-cast austenitic stainless steel and found that the size of NbC did not DOI: 10.1002/srin.202400176…”
Section: Introductionmentioning
confidence: 99%